2012
DOI: 10.3109/1354750x.2012.737025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of fibronectin 1 (FN1), integrin α4β1 (ITGA4), syndecan-2 (SDC2), and glycoprotein CD44 as the potential biomarkers of oral squamous cell carcinoma (OSCC)

Abstract: FN1 and ITGA4 are potential OSCC biomarkers for tongue/mouth floor and edentulous ridge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 67 publications
3
55
0
1
Order By: Relevance
“…It has been demonstrated that the expression of FN1 proteins was closely related with the development of various malignant tumors of oral squamous cell carcinoma, nasopharyngeal carcinoma, ovarian cancer, renal cancer, and thyroid cancer. [15][16][17][18][19] However, the previous studies did not clarify the roles of FN1 in CRC behaviors. In this study, we identified FN1 as a potential oncogene in CRC based on analysis of public datasets and clinical subjects and investigated the effects of FN1 on the biological behavior of CRC cells in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated that the expression of FN1 proteins was closely related with the development of various malignant tumors of oral squamous cell carcinoma, nasopharyngeal carcinoma, ovarian cancer, renal cancer, and thyroid cancer. [15][16][17][18][19] However, the previous studies did not clarify the roles of FN1 in CRC behaviors. In this study, we identified FN1 as a potential oncogene in CRC based on analysis of public datasets and clinical subjects and investigated the effects of FN1 on the biological behavior of CRC cells in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…cDNA was reacted with iQ SYBR Green Supermix (Bio‐Rad Laboratories, Hercules, California) for preforming Real‐Time RT‐PCR using a MyiQ real‐time machine (Bio‐Rad). Epithelial‐mesenchymal transition (EMT) signaling such as focal adhesion kinase ( FAK ), E‐cadherin ( E‐cad ), Slug , twist‐related protein 1 ( Twist ), vimentin ( Vim ), N‐cadherin ( N‐cad ), and GAPDH genes were studied by a touch‐down PCR program (50 cycles) 28 . The primer and PCR amplicon information 29–32 is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, identifying reliable biomarkers to predict disease-specific survival (DSS) and the recurrence of OSCC is an emerging issue. To date, many studies have attempted to identify novel biomarkers for OSCC, such as fibronectin 1 (FN1) [22], integrin alpha4beta1 (ITGA4) [22], syndecan-2 (SDC2) [22], glycoprotein CD44 [22], AXL [23], matrix metalloproteinases (MMP) 1 and MMP10 [24]. However, many of these studies are limited to the gene expression or protein levels due to a small numbers of patients.…”
Section: Introductionmentioning
confidence: 99%